Imam Fakhr al-Dīn al-Rāzī’s Critiques of Qāḍī ʿAbd al-Jabbār al-Muʿtazilī’s views: (An Analytical Case Study on the Ruling of Major Sins) - Janbaz Durrani; Prof. Dr Taj Afsar; Dr. Rahim Ullah (Journal of Religion and Society, 2025)
The Qur’an constitutes a decisive turning point, not only in the history of religion and religious civilization, but also in the history of thought and knowledge in their religious, scientific, and philosophical dimensions. This is due to its encompassing of the divine foundations and principles that guide human understanding, in such a way that revelation, together with existence itself, becomes both a source and a starting point for the human intellect in its pursuit of knowledge and learning. This intellectual framework was further enriched by the massive translation effort undertaken by the enormous Muslim empires in the mid-eighth century. Ancient Greek, Persian, Latin and Indian works were translated into Arabic, primarily at “Bayt al- Ḥikmah in Baghdad”. The works of Socrates, Aristotle, and Plato were rendered as well. The result of this was the rise and emergence of many Islamic intellectual movements and philosophical doctrines, each distinguished by its leading figures, theoretical frameworks, and distinctive features. The Mu'tazila represents the first broad school of theology to appear in Islam distinguished by emphasizing on reason and rational thought. This article is an attempt to shed light on the basics of this movement highlighting one of their principle beliefs (The Intermediate position or Al-manzila bynal manzilatain) demonstrating Imam Razi’s critiques of Qadi Abdul Jabbar al Mutazili’s views in his Commentary known as “Mafāṭīḥ al-Ġhyb’’ Keywords: Critique, Mu’tazila, Al-Razi, Abdul Jabbar, Major Sins